The requirement of plant variety protection in TRIPS and its importance for the cut flower export industry in developing countries - De Jong, Annemarie (Intellectual Property Research Unit, 2014)
This paper addresses the issue of protection of plant varieties under the agreement on Trade-Related Aspects of Intellectual Property Rights. It describes the origins of plant variety protection, discusses the available options for developing countries and looks at the current status of compliance with the TRIPS provisions. Against this background the relationship between plant variety protection and global trade is analysed for one particular aspect: the cut flower export industry in developing countries.